2023
DOI: 10.3390/electronics12132925
|View full text |Cite
|
Sign up to set email alerts
|

Constructing Maps for Autonomous Robotics: An Introductory Conceptual Overview

Abstract: Mapping the environment is a powerful technique for enabling autonomy through localization and planning in robotics. This article seeks to provide a global overview of actionable map construction in robotics, outlining the basic problems, introducing techniques for overcoming them, and directing the reader toward established research covering these problem and solution domains in more detail. Multiple levels of abstraction are covered in a non-exhaustive vertical slice, starting with the fundamental problem of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…These advancements hold promise for enhancing the efficiency and capabilities of unmanned guided vehicles across various industrial applications. SLAM technology has transcended its traditional industrial applications and found utility beyond factory settings [6,7]. For instance, iRobot's Roomba 980 cleaning robot efficiently navigates rooms using SLAM technology [8].…”
Section: Introductionmentioning
confidence: 99%
“…These advancements hold promise for enhancing the efficiency and capabilities of unmanned guided vehicles across various industrial applications. SLAM technology has transcended its traditional industrial applications and found utility beyond factory settings [6,7]. For instance, iRobot's Roomba 980 cleaning robot efficiently navigates rooms using SLAM technology [8].…”
Section: Introductionmentioning
confidence: 99%